INTERNATIONAL LAW AND PROCEDURAL SAFEGUARDS IN DEPORTATION PROCEEDINGS: AHANI V. CANADA - Heckman, Gerald (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2004)
In Ahani v. Canada, the United Nations Human Rights Committee considered the procedural and institutional rights conferred by the International Covenant on Civil and Political Rights on aliens who face deportation on national security and other grounds. By “reading in” some of the due process protections reflected in article 14 of the Convention, the decision gave meaningful content to an alien’s article 13 right to submit reasons against his expulsion and to have his case reviewed by a competent authority. These include the right to sufficient notice of the case so that the alien can resist removal, accompanied by appropriate disclosure, and the right to reasons for the final removal decision. Unfortunately, the decision failed to determine whether article 14 applied directly to immigration decision-making, entitling aliens to a hearing before an independent and impartial tribunal. The author argues that the Committee should have addressed this question and found, in light of the travaux préparatoires of the Covenant, the Committee’s jurisprudence, and that of the European Court of Human Rights, that article 14 does apply to some immigration decision-making, including deportation proceedings.